Integrated Microbiology and Metabolomics Analysis Reveal Responses of Soil Bacterial Communities and Metabolic Functions to N-Zn Co-Fertilization in the Rhizosphere of Tea Plants (Camellia sinensis L.) - Min Lu; Yali Shi; Dandan Qi; Qiong Wang; Haowen Zhang; Ying Feng; Zhenli He; Chunwang Dong; Xiaoe Yang; Changbo Yuan (Plants, 2025)
The co-fertilization of nitrogen (N) and zinc (Zn) offers significant advantages in improving the growth and development of tea plants (Camellia sinensis L). However, the corresponding responses of rhizosphere microecology remain unclear. In this study, a pot experiment was performed to investigate the effects of N-Zn co-fertilization on rhizosphere soil’s N availability, the rhizobacterial community and the metabolism of tea plants. N-Zn co-fertilization significantly increased the soil total of N, NH4+-N and NO3−-N contents. 16S rRNA sequencing found that N-Zn co-fertilization recruited rhizobacteria associated with N cycling and Zn activation, including Proteobacteria, Acidobacteriota and Gemmatimonadota, resulting in complex rhizobacterial networks. Metabolomics analysis indicated obvious interferences in the metabolisms of lipids, amino acids and cofactors and vitamins after fertilization. PLS-PM analysis suggested that fertilization had both direct and indirect influences on the rhizobacterial community and differential metabolites. RDA models identified pH (R2 = 0.734, p < 0.01; R2 = 0.808, p < 0.01) and total N (R2 = 0.633, p < 0.05; R2 = 0.608, p < 0.01) as dominant factors influencing both the rhizobacterial community and differential metabolites. Finally, network analysis found significant associations between rhizobacteria related to N cycling and Zn mobilization and metabolic processes involved in N metabolism and responses to Zn stress. These findings underscored that appropriate N-Zn co-fertilization is crucial for the rhizosphere soil’s N availability and the microenvironment of tea plants.